The evolution of the check as a means of payment: A historical survey - Stephen Quinn; William Roberds (Economic Review, 2008)
Though checks' popularity is now waning in favor of electronic payments, checks were, for much of the twentieth century, the most widely used noncash payment method in the United States. How did such a relatively inefficient form of payment become so dominant? This article traces the historical evolution of the check, focusing on its relation to complementary and competing payment technologies. Originating in the eastern Mediterranean during the first millennium as a convenient form of payment between local merchants, checks became more versatile through the development of negotiability in sixteenth-century Europe. The suppression of banknotes in eighteenth-century England further promoted the use of checks. In the United States, nineteenth-century legislation discouraged other payment methods and eventually led to a nationwide check payment system. In the twentieth century, under the Federal Reserve's leadership, checks expanded rapidly and became the nation's default payment method. The authors discuss some persistent historical themes surrounding checks: checks' ease of use, which provides advantages over other payment methods but creates risk to businesses and banks; checks' sophistication, which evolved through centuries of legal precedent and operational experimentation; and checks' high costs relative to other forms of payment. Checks' traditional dominance of the U.S. payment system, the authors conclude, resulted from historical happenstances. These events gave the check relative advantages that are only now being overcome by electronic payment technologies.
Keywords: E42; G21; N10; 330; checks; payments; Federal Reserve; banknotes; bills of exchange; Scheck; Geldgeschichte; Zahlungsverkehr; USA; Welt